Pentahelix Collaboration in Improving Taxpayer Compliance - Notika Rahmi; Selvi Selvi; Agitta Sofyan Purwaningtyas (Ilomata International Journal of Tax and Accounting, 2022)
The government has made various efforts to improve taxpayer compliance but the efforts that have been made have not been effective enough. Collaboration between stakeholders is needed in harmonizing and synergizing all components of taxpayers. This study was conducted with the aim of analyzing pentahelix collaboration in improving taxpayer compliance at Cimanggis Tax Office. The study used descriptive qualitative methods with data collection techniques through observation, interviews and literature study. The results of the study show that collaboration has been carried out by the government well by involving various parties who take an active role, namely the private sector, academia, the media and the community. Each party has its own role in helping improve taxpayer compliance. In its implementation there are several obstacles, but coordination continues to be carried out together to carry out the commitments that have been made.